The Organization of Islamic Cooperation in contemporary international society - Víctor Luis Gutiérrez Castillo (Revista Electrónica de Estudios Internacionales, 2014)
The Organisation of Islamic Cooperation (OIC) is an international organisation consisting of 57 member States of Muslim confession, also Palestina. This organisation is "the collective voice of the Muslim world" and works to "safeguard and protect the interests of the Muslim world in the spirit of promoting international peace and harmony". In 28 June 2011 during the 38th Council of Foreign Ministers meeting (CFM) in Astana (Kazakhstan) the organisation changed its name from Organisation of the Islamic Conference to its current name.The OIC also changed its logo at this time.The Organisation of Islamic Cooperation (OIC) has a permanent delegation of the United Nations and it’s the second largest international organisation outside the United Nations. In recent years it has been increasing its importance in the international society and it has played an important role in regional conflicts